The Evaluation of the Competence of Expert Supervisory Consultants in the Implementation of Construction Projects - Viana, Nazella Putri; Suraji, Akhmad; Hidayat, Benny (CIVED, 2024)
The success in the implementation of construction projects is determined by the quality of the people involved in handling them, especially those who play an important role in the process of implementing construction projects such as supervisory consultants, supervisory consultants must meet the necessary criteria. In addition, the competence of supervisory consultants is very important so that the implementation of construction projects can produce good performance. Competence of supervisory consultants can improve performance in project implementation. supervisory consultants who carry out strategic supervision such as choosing the necessary implementation methods, as well as providing the best solution if there are obstacles or obstacles in the implementation of construction projects. The formulation of the problem in this study is to find out how the classification of the competence of supervisory consultants on construction projects and find out what are the competency factors possessed by supervisory consultants on the implementation of construction projects. The method of data collection carried out is by means of literature studies and surveys on the required sources of information in the form of interviews and research instruments, namely questionnaires in the form of multiple choice questions consisting of 100 items for each expert. Data analysis was carried out with statistics using the help of the Microsoft excel program and the SPSS Version 23 program.